Dorsal or Lateral Approach for Intramedullary Nailing Using Kirschner Wire in Pediatric Radius Diaphyseal Fractures: Does it really matter? - AKGÜLLE, AHMET HAMDİ; ŞİRİN, EVRİM; KESİMER, MEHMET DENİZ; TOPKAR, OSMAN MERT (SPRINGER HEIDELBERG, 2021)
Background Intramedullary nailing is the most preferred fixation method for diaphyseal radius and ulna fractures in the young age group. The aim of this study was to compare the dorsal and lateral entry points in the context of entry site-related complications, fracture union and functional results. Methods This retrospective comparative study included pediatric patients who underwent surgery for isolated diaphyseal radius or both bone forearm fractures with intramedullary nailing using Kirschner wire between January 2013 and January 2019. K-wire was introduced from the distal radius through dorsal entry (Group A) in 19 patients and lateral entry (Group B) in 18 patients. The mean follow-up was 37 months. Complications were noted and functional outcomes were evaluated according to the CHOP criteria. Results All fractures were healed. The functional results were determined to be excellent for 30, fair for 4, and poor for 3 patients. The overall complication rate was 18.9%, including distal radius fracture, mild pain in the wrist, and minor loss in ROM. No statistically significant differences were determined between the groups in respect of functional results and complication rates. Conclusion Good functional results and similar complication rates can be obtained with both dorsal and lateral entry approaches. Stainless steel K-wire is an inexpensive intramedullary fixation implant option, which provides strong stabilization. Distal radius fracture is a newly reported complication for forearm intramedullary nailing. Leaving the implant out of the skin seems safe with the benefit of avoiding a further surgical intervention to extract the implant.
Keywords: Pediatric forearm fractures; Intramedullary nailing; Dorsal or lateral approach